Ways to Improve the Professional and Methodological Competencies of Future Biology Teachers - Salimova Sarvinoz Farxodovna (European International Journal of Pedagogics, 2025)
Developing professional and methodological competencies is critical for future biology teachers preparing to navigate the complexities of contemporary classrooms. This study investigates strategies aimed at enhancing prospective educators’ abilities to plan effective lessons, apply diverse instructional methods, and foster scientific inquiry among students. A mixed-method design was used to explore the impact of targeted training modules, microteaching sessions, and collaborative reflection on pre-service teachers’ pedagogical growth. Quantitative findings demonstrated a statistically significant increase in lesson quality and content mastery following the intervention, while qualitative data revealed heightened self-confidence and improved classroom management strategies. Results underscore the importance of well-structured teacher preparation programs that integrate both theoretical and hands-on learning experiences. Recommendations include expanding inquiry-based activities, fostering interdisciplinary collaboration, and providing continuous feedback through peer mentoring. These findings contribute to ongoing discourse on teacher education and offer practical insights into refining teacher-training curricula in the field of biology.